Secularizing Islamists? Jama'at-e-Islami and Jama'at-ud-Da'wa in urban Pakistan - Iqtidar, Humeira (South Asia across the disciplines, 2011)
Offers an analysis of two Islamist parties in Pakistan, the Jama'at-e-Islami and the more militant Jama'at-ud-Da'wa, widely blamed for the November 2008 terrorist attack in Mumbai, India. The author proposes that these Islamists are involuntarily facilitating secularization within Muslim societies, even as they vehemently oppose secularism